PEMBELAJARAN MATEMATIKA BERBASIS INFORMATIKA - Khusnul Khotimah (Universitas Muhammadiyah Kotabumi, 2017)
The Mathematic Teaching and learning based informatic system is learning system implementing computerization technology as a learning tool in theteaching and learning process. This teaching and learning process in which it combines conventional method with the application practice has been constructed on the basis of the implemented curriculum in a college. The use of media in a teaching and learning process like computer as a learning tool will make the teaching and learning process more effective because it will create an interesting teching and learning process as well as stimulate the students’ creativity. In addition, the teaching and learning process not only as a tutorial qctivity but also it provides the implentation of the theories given. The Mathematic teaching and learning based informatic is done to know the comparison of problem solving in mathematic using Mathematic software application. The standardized process and the use of informatic are constructed based on the exsisting curriculum in order to control the quality of the learning proses and result.